2013
DOI: 10.1021/ac303328g
|View full text |Cite
|
Sign up to set email alerts
|

Portable Capillary Electrophoresis Instrument with Automated Injector and Contactless Conductivity Detection

Abstract: A portable capillary electrophoresis instrument featuring an automated, robust, valve-based injection system was developed. This significantly facilitates operation in the field compared to previous injection approaches. These generally required delicate manual operations which are difficult to perform outside the laboratory environment. The novel system relies on pressurized air for solution delivery and a micromembrane pump for sample aspiration. Contactless conductivity detection was employed for its versat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 37 publications
1
79
0
Order By: Relevance
“…Then, different solutions were prepared by serial dilution in the concentration ranges between 0120 µmol L -1 for chloride, nitrate and nitrite and 060 µmol L -1 for sulfate. All of them were analyzed on ME devices under the same experimental conditions and the resulting electropherograms are displayed in supplemental Figure S3 study are comparable to the values reported in literature using ME-C 4 D [33,48], lower than the values adopted by AOAC using IC methods [5] and higher than values achieved with electrophoresis chips coupled with contact conductivity detection [49] or through a portable capillary electrophoresis instrument equipped with C 4 D [50].…”
Section: Insert Figuresupporting
confidence: 72%
“…Then, different solutions were prepared by serial dilution in the concentration ranges between 0120 µmol L -1 for chloride, nitrate and nitrite and 060 µmol L -1 for sulfate. All of them were analyzed on ME devices under the same experimental conditions and the resulting electropherograms are displayed in supplemental Figure S3 study are comparable to the values reported in literature using ME-C 4 D [33,48], lower than the values adopted by AOAC using IC methods [5] and higher than values achieved with electrophoresis chips coupled with contact conductivity detection [49] or through a portable capillary electrophoresis instrument equipped with C 4 D [50].…”
Section: Insert Figuresupporting
confidence: 72%
“…Note, that some of these performance parameters very much depend on how the separation procedure has been optimized (i.e. either for high separation efficiency, fast analysis time, wide dynamic range, or low limits of detection, see for example 29, 30) and a comparison between different quoted performance values for C 4 D is hampered by this fact.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, the method was also known for its poor precision due to inconsistent injection volume, variability of electrophoresis conditions inside of the capillary and the interaction of the analyte with the capillary wall . Although efforts have been made to overcome these difficulties and to convince the scientific community in high analytical merits of CE yet common equipment and protocols are still considered as less precise and less reproducible than in chromatography.…”
Section: Chiral Separation By Cementioning
confidence: 99%